TI_GERICHTE 12.2014.20 vom 23. Juni 2015 , Contratto di gestione patrimoniale - responsabilità del mandatario - calcolo del danno - TI Tribunale d'appello (2015)
Contratto di gestione patrimoniale - responsabilità del mandatario - calcolo del danno